Enhancement in piezoelectric sensitivity via negative structural stiffness. (November 2016) - Kalathur, Harshavardhan; Lakes, Roderic
Effective piezoelectric sensitivity of bimorph strip actuators was enhanced by negative structural stiffness. Negative stiffness was achieved in brass strips post-buckled in compression to an "S" shape; the brass strip was placed in series with the bimorph. The negative stiffness was tuned by adjusting the brass strip length. The effective piezoelectric sensitivity in units of displacement per volt input increased as the inverse of the overall stiffness of the series element. The maximum observed enhancement in effective piezoelectric sensitivity was at least a factor of 6 at 1 Hz in comparison with the value when no negative stiffness was used. This corresponds to a maximum effective sensitivity of about 36 µm/V in comparison with the baseline effective sensitivity of about 6.1 µm/V at 1 Hz. The value is several orders of magnitude (almost 40, 000 times) higher than the typical value of sensitivity for the material comprising the individual bimorph strip actuator.